2016
DOI: 10.1371/journal.pone.0161968
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Transfected Cells Expressing Low-Incidence Blood Group Antigens: Novel Methods Facilitating Their Use as Reagent-Cells

Abstract: BackgroundThe identification of erythrocyte antibodies in the serum of patients rely on panels of human red blood cells (RBCs), which coexpress many antigens and are not easily available for low-incidence blood group phenotypes. These problems have been addressed by generating cell lines expressing unique blood group antigens, which may be used as an alternative to human RBCs. However, the use of cell lines implies several drawbacks, like the requirement of cell culture facilities and the high cost of cryopres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, these problems probably could be solved by the use of lyophilized transfected cells. 28 Interestingly, variable clinical pictures of FNAIT mediated by anti-CD36 isoantibodies, including mild and severe thrombocytopenia, hydrops fetalis, and recurrent abortions, have been observed. [9][10][11][12][13]29 However, the precise mechanism of this phenomenon is not known.…”
Section: Discussionmentioning
confidence: 99%
“…However, these problems probably could be solved by the use of lyophilized transfected cells. 28 Interestingly, variable clinical pictures of FNAIT mediated by anti-CD36 isoantibodies, including mild and severe thrombocytopenia, hydrops fetalis, and recurrent abortions, have been observed. [9][10][11][12][13]29 However, the precise mechanism of this phenomenon is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Although we preliminarily confirmed that differentiated HiDEP‐1 cells could maintain antibody detectability for at least 1 week at 4°C in erythroid differentiation medium or several months frozen in a cryopreservation medium (data not shown), the storage conditions should be optimized using appropriate preservation solutions such as Alsever's solution to improve their storage stability, taking RBC shelf life into consideration. In addition, stabilization of surface antigens by chemical fixing has been well studied, and fixation with a preservation reagent could stabilize the antigen for more than 100 days . These preservation methods may also be applied to stabilize blood group antigens on HiDEP‐1 cells and extend their shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stabilization of surface antigens by chemical fixing has been well studied, 21,22 and fixation with a preservation reagent could stabilize the antigen for more than 100 days. 23 These preservation methods may also be applied to stabilize blood group antigens on HiDEP-1 cells and extend their shelf life. Third, HiDEP-1 cells were prone to forming a red cloudy background in the test tube.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of cell lines implies several drawbacks including the need of cell culture facilities and cryopreservation; this work is most probably comprehensible for diagnostic laboratories due to the fact that these cell lines can be fixed and used after 4 weeks of storage at 4°C. Recent study demonstrated that the addition of cell stabilizers (such as TransFix reagent) or lyophilizing of cells using trehalose could extend the stability of low‐frequency blood group antigens (Di a and Lu a ) expressed on the surface of CHO cells . In spite of short‐lived neutrophils, stable transfected FcγRIIIb cell lines are advantageous; these cell lines express definable amounts of FcγRIIIb which do not vary among different individuals such as neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study demonstrated that the addition of cell stabilizers (such as TransFix reagent) or lyophilizing of cells using trehalose could extend the stability of low-frequency blood group antigens (Di a and Lu a ) expressed on the surface of CHO cells. 26 In spite of short-lived neutrophils, stable transfected FcgRIIIb cell lines are advantageous; these cell lines express definable amounts of FcgRIIIb which do not vary among different individuals such as neutrophils. Copy number variation of FcgRIIIb correlates with the capacity of neutrophils to phagocytose immune complexes has been described.…”
Section: Discussionmentioning
confidence: 99%